Cinematography. 65 mm and 70 mm film. Sound. Specification for the location and dimensions of six-track magnetic sound records on 70 mm motion-picture release prints with magnetic stripes Part 4.4.1, (15th July 1992) - British Standards Institution,
No abstract available